Impact of vancomycin protein binding on target attainment in critically ill children: back to the drawing board?. (15th December 2016) - De Cock, Pieter A. J. G.; Desmet, Sarah; De Jaeger, Annick; Biarent, Dominique; Dhont, Evelyn; Herck, Ingrid; Vens, Daphné; Colman, Sofie; Stove, Veronique; Commeyne, Sabrina; Vande Walle, Johan; De Paepe, Peter
Abstract : Objectives: The objectives of this observational study were to investigate plasma protein binding and to evaluate target attainment rates of vancomycin therapy in critically ill children. Patients and methods: Paediatric ICU patients, in whom intravenous intermittent dosing (ID) or continuous dosing (CD) with vancomycin was indicated, were included. Covariates on unbound vancomycin fraction and concentration were tested using a linear mixed model analysis and attainment of currently used pharmacokinetic/pharmacodynamic (PK/PD) targets was evaluated. Clinicaltrials.gov: NCT02456974. Results: One hundred and eighty-eight plasma samples were collected from 32 patients. The unbound vancomycin fraction (median = 71.1%; IQR = 65.4%–79.7%) was highly variable within and between patients and significantly correlated with total protein and albumin concentration, which were both decreased in our population. Total trough concentration (ID) and total concentration (CD) were within the aimed target concentrations in 8% of patients. The targets of AUC/MIC ≥400 and f AUC/MIC ≥200 were achieved in 54% and 83% of patients, respectively. Unbound vancomycin concentrations were adequately predicted using the following equation: unbound vancomycin concentration (mg/L) = 5.38 + [0.71 × total vancomycin concentration (mg/L)] − [0.085 × total protein concentration (g/L)]. This final model was externally validated using 51 samples from another six patients. Conclusions: The protein binding of vancomycin in our paediatric population was lower than reported in non-critically ill adults and exhibited large variability. Higher target attainment rates were achieved when using PK/PD indices based on unbound concentrations, when compared with total concentrations. These results highlight the need for protein binding assessment in future vancomycin PK/PD research.